1993
DOI: 10.1111/j.1399-302x.1993.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Porphyromonas gingivalis toward cultured human gingival fibroblasts

Abstract: Direct cytotoxicity of black-pigmented anaerobic rods was studied on the confluent monolayer of human gingival fibroblasts in vitro. Only strains of Porphyromonas gingivalis caused morphological alteration (cell-rounding) and notable depression of viability of fibroblasts. To determine the location of the cytotoxicity, bacterial surface components, i.e., outer membrane, lipopolysaccharide, fimbriae and outer membrane vesicles were prepared from P. gingivalis and their cytotoxicity was assessed. Among these pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…We used two in vitro models of P. gingivalis – host cell interaction. First, we used a cellular cytotoxicity assay (22, 25) where P. gingivalis (strain W83) was added to confluent cell cultures resulting in morphological changes in both the oral epithelial cell line OKF6/TERT-2 and in HGEC. These changes included loss of adhesion, cell rounding, and detachment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used two in vitro models of P. gingivalis – host cell interaction. First, we used a cellular cytotoxicity assay (22, 25) where P. gingivalis (strain W83) was added to confluent cell cultures resulting in morphological changes in both the oral epithelial cell line OKF6/TERT-2 and in HGEC. These changes included loss of adhesion, cell rounding, and detachment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HGFs were obtained from a gingival biopsy of a 20-year-old person with clinically healthy periodontium and maintained according to the method of Morioka et al [9]. The cells from passages 10^14 were used for the following experiments.…”
Section: Preparation Of Hgf Measurement Of Il-6 and Il-8 Secretion mentioning
confidence: 99%
“…35 In this study we demonstrated that proliferation of human PDL cells was reduced significantly by the treatment of the cells with a P. gingivalis extract, as observed in gingival fibroblasts. [26][27] The highest concentration of bacterial extract (100 pg/mL) inhibited cell proliferation completely, caused cell death, and altered cell morphology. The presence of P. gingivalis at higher concentrations may directly destroy the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial components, such as surface-associated material, outer membrane, outer membrane vesicles, and fimbriae from outer membrane were able to cause either growth inhibition or cytotoxicity in fibroblasts. [25][26] Our bacterial extract contained all these factors, except for outer membrane vesicles which are normally obtained from the supernatant of the culture. Proteolytic enzymes, such as collagenases and aminopeptidases, have long been considered pathogens since periodontal tissues consist mostly of collagen, which is a substrate for these enzymes.26-28 If proteolytic enzymes in our P. gingivalis extract changed cell surface molecules, degradation of PDGF-R in the membrane may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation